Fetal age at death estimation on dry bone: testing the applicability of equations developed on a radiographic sample - Carneiro, Cristiana (2019)
The paucity of identified skeletal collections that include fetuses entails the need to pursue unconventional approaches and resources in order to investigate fetal anatomical variation. Radiographic analyses are being considered as a good alternative to data obtained in osteological collections. In a previous work, we developed equations to estimate gestational age (GA) at death by measuring fetal long bones on x-rays. This study aims to test the applicability of these equations in dry bones, and to assess its accuracy and bias. A test sample of 17 fetuses with known gestational age at death from the osteological collection of the Department of Legal Medicine, Toxicology and Physical Anthropology, Faculty of Medicine of the University of Granada (Spain) was employed. Examined bones comprised the femur, tibia, humerus and radius. The proposed models show high accuracy and low bias in the assessment of gestational age at death in a sample of fetal dry bones. The new equations, especially those obtained with classical calibration, are a valuable tool to estimate fetal gestational age at death in both forensic and archeological contexts.